2012
DOI: 10.2214/ajr.11.7750
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of MRI in Differentiating Hepatocellular Adenoma From Focal Nodular Hyperplasia: Prospective Study of the Additional Value of Gadoxetate Disodium

Abstract: This study shows high sensitivity of gadoxetate disodium-enhanced MRI when standard series are combined with the hepatobiliary phase for differentiation of FNH and HCA in lesions larger than 2 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 31 publications
4
94
0
1
Order By: Relevance
“…A lobular border is often described as a typical sign for the diagnosis of FNH, but our research group and others have found that the occurrence of a lobular border is not uncommon in HCAs (21,22).…”
Section: Conventional Mri Findings For Hepatocellular Adenomamentioning
confidence: 61%
See 1 more Smart Citation
“…A lobular border is often described as a typical sign for the diagnosis of FNH, but our research group and others have found that the occurrence of a lobular border is not uncommon in HCAs (21,22).…”
Section: Conventional Mri Findings For Hepatocellular Adenomamentioning
confidence: 61%
“…The surrounding liver steatosis, intralesional fat accumulation, faint arterial enhancement pattern and presence of multiple lesions are more or less typical for HCA but can also occur in FNH (21)(22)(23). A lobular border is often described as a typical sign for the diagnosis of FNH, but our research group and others have found that the occurrence of a lobular border is not uncommon in HCAs (21,22).…”
Section: Conventional Mri Findings For Hepatocellular Adenomamentioning
confidence: 61%
“…A prospective study of histopathologic analyses of 54 focal liver lesions larger than 2 cm (24 FNH and 28 HCA) found that, as compared with GdDTPA, GdEOBDTPA was associated with increased diagnostic sensitivity for both HCA (50% vs 96%) and FNH (68% vs 96%). Bleeding, fat, and glycogen were more commonly present in adenomas, whereas a central scar was predictive of FNH (62) . A retrospective histopathologic study of 115 focal liver lesions (44 FNH and 71 HCA) concluded that the presence of contrast uptake of FNH vs. hypointensity of HCAs in the hepatobiliary phase yielded an accuracy of 92% for differential diagnosis of these lesions (63) .…”
Section: Focal Nodular Hyperplasia and Liver-specific Contrast Agentsmentioning
confidence: 92%
“…Presence of enhanced T2 weight images that further enhance on gadolinium administration is highly characteristic of HCA [25] . Studies of late have tried to characterize these lesions into its four genotypic types based on MRI features.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…In comparison to the existing gadolinium-based contrast agents for MRI, gadobenate dimeglumine or gadoxetate disodium enhanced liver MRI (hepatobiliary specific contrast agents) have both renal and hepatobiliary clearance. Owing to variable contrast uptake observed in hepatobiliary phase, HCA (being hypointense) can be differentiated from FNH (being iso-or hyperintense on delayed imaging) [25] .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%